(untitled) (Research, Society and Development, 2022)
Objectives: To verify the scientific evidence on the role and performance of nurses in the early detection of Autism Spectrum Disorder (ASD). Methods: This is an Integrative Review study that aims to synthesize results obtained in research on a topic or issue. The literature search began in August 2022, in the electronic databases: Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online, Database in Nursing, consulted through the Virtual Health Library and Scientific Electronic Library Online. 262 articles were selected after adding the inclusion criteria, remaining 15 articles. Results: For a better understanding of the results, a table with a summary of the studies was prepared, including author/year of publication, title, objectives, type of study, and the main results. It was evidenced that the nurses’ knowledge about the role of nursing in the early detection of the Autism Spectrum Disorder is fundamental, because such knowledge can serve as support in strategic and operational planning and encourage reflection and awareness of the importance of the signs and symptoms in the first months of life of the child with ASD and avoid possible aggravations. Conclusion: The research had great relevance because there is a need for knowledge of nursing professionals about the early detection of autism in children under two years of age and for the belief that there are new methods and practices to be used.